Charles H. Collis papers - Collis, Charles H. T. (Charles Henry Tucky), 1838-1902.
Volume containing morning reports (1861 August 25-1862 May 21) for Collis's company of Zouaves d'Afrique (later to become Co. A of the 114th Pennsylvania) in Maryland and Virginia.
Collection material in English.
Keywords: United States. -- Army. -- Pennsylvania Infantry Regiment, 114th (1862-1865); Maryland -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.